Cohomological correlations for sets of singular points of the actions of Z/4 group by (S^n)^k - Plakhta , L. P. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We investigate Z/2-graded cohomology modules with coefficients in the field F_2 of sets of singular points of the complex actions of the group Z/4 on spaces X whose cohomology rings are isomorphic to H* ((S^n)^k, F_2).